KASHMIR UNDER THE SULTANS - Hasan, Mohibbul. ([S.l.])
1 online resource
Keywords: Kashmir Under Sultansintroduces the reader to a subject that begins with the foundation of the Sultanate and ends with the conquest of Kashmir by Akbar. During the Sultanate period, Kashmir had achieved a high standard of culture, but with the disappearance of her independence, her culture gradually declined. Poets, painters, and scholars had to leave the Valley and seek their livelihood elsewhere owing to the absence of local patronage. They then entered the service of the Mughal emperors and were added to the court, thereby lessening the cultural impoverishment of Kashmir. The book encloses political, social, economic and cultural activities that had a lasting influence on the Kashmir Valley in that period. It is of considerable value to social historians as Professor Mohibbul Hasan offers insights into political and cultural currents and crosscurrents in Kashmir. This title is co-published with Aakar Books. Print editions not for sale in South Asia (India, Sri Lanka, Nepal, Bangladesh, Pakistan and Bhutan)